Analysis of Wages in Improving Employee Performance at PT. Gunung Melayu - Asian AGRI - Putri Ardyanti, Cici; Yenni Samri Juliati Nasution; Nurwani (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Employees are a very important role in the company PT Gunung Melayu - Asian Agri to increase the production that the company wants to achieve. Labor is the second most important factor of production, because it is through the services of labor that natural resources can be converted into valuable products. There are attributes that exist and are related to work. This study aims to determine wages in improving employee performance at PT Gunung Melayu Asian Agri. This research was conducted using a qualitative method with data collection methods using interviews, observation and documentation. The data sources used are primary data and secondary data. The results of this study indicate that wages can improve employee performance. Where wages, both in the form of bonuses and basic wages can improve employee performance.